How can a wholesale market with multipurpose spaces in Pillcomarca contribute to society? - Daga-Almerco, Bekin B. (2024)
The purpose of the research is to satisfy the needs of the population through the design of a sustainable wholesale market with multipurpose spaces in the Pillco Marca district, in this way the population will be able to access a required service or good, that is, the products or services provided by the infrastructure, meet the wishes and requirements of the user. The methodology used in the research was a documentary research methodology, where bibliographic reviews of different authors were made to collect information. The most notable results show that it is not pleasant to make a purchase under current conditions. So encouraging a multi-purpose, forward-thinking market design of this type of infrastructure, advocating for a better and more sustainable relationship with the changing environment is essential, using appropriate construction materials to reduce environmental pollution as this is positive for the population and also for use and consumption.